Effectiveness of a Planned Teaching Programme on Primigravid Mothers' Awareness of Specific Natural Pain Relief Techniques Used During Labor in Particular Bangalore Hospital - Usha Rani R.; Vijayalakshmi (International Journal of Midwifery Nursing And Practices, 2023)
Background: Pain is an exciting sensation and is caused by the stimulus during labor. Always Pain plays a major role in labor in empowering the women, whereby they triumph by giving delivery to the newborn. Objectives: Assess the knowledge level about selected natural pain relief methods. Methodology: A quantitative research approach and the design used in this study was a pre-experimental research design. Sixty primigravid mothers were selected for the study through a purposive sampling technique. The information from the subjects was gathered using a planned interview schedule. Results: Most women 47 (78.03%) had insufficient understanding of natural pain management techniques prior to the pretest. Most of the mothers, that is 38 (63.3%) of them, performed adequately on the post-test. When compared to their pre-test knowledge of natural pain management techniques (mean score 10.32), most mothers performed better on the post-test (mean score 21.43). The structured teaching program using charts and demonstrations is a very effective way to increase knowledge of pain treatment techniques
Keywords: effectiveness; labor; natural pain relief methods; primigravid mother; structured teaching program